Bioconstitutional Imaginaries and the Comparative Politics of Genetic Self-knowledge. (November 2020) - Hurlbut, J. Benjamin; Metzler, Ingrid; Marelli, Luca; Jasanoff, Sheila
Genetic testing has become a vehicle through which basic constitutional relationships between citizens and the state are revisited, reaffirmed, or rearticulated. The interplay between the is of genetic knowledge and the ought of government unfolds in the context of diverse imaginaries of the forms of human well-being, freedom, and flourishing that states have a duty to support. This article examines how the United Kingdom, Germany, and the United States governed testing for Alzheimer's disease, and how they diverged in defining potential harms, benefits, and objects of regulation. Comparison before and after the arrival of direct-to-consumer genetic tests reveals differences in national understandings of what it means to protect life and citizenship: in the United Kingdom, ensuring physical wellness through clinical utility; in the United States, protecting both citizens' physical well-being and freedom to choose through a framework of consumer protection; and in Germany, emphasizing individual flourishing and an unburdened sense of human development that is expressed in genetic testing law and policy as a commitment to the stewardship of personhood. Operating with their own visions of what it means to protect life and citizenship, these three states arrived at settlements that coproduced substantially different bioconstitutional regimes around Alzheimer's testing.